2020
DOI: 10.1080/17453674.2020.1818175
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial comparing suture button with single 3.5 mm syndesmotic screw for ankle syndesmosis injury: similar results at 2 years

Abstract: Background and purpose — Better outcomes are reported for suture button (SB) compared with syndesmotic screws (SS) in patients treated for an acute ankle syndesmotic injury. One reason could be that screws are more rigid than an SB. A single tricortical 3.5 mm syndesmotic screw (TS) is the most dynamic screw option. Our hypothesis is that 1 SB and 1 TS provide similar results. Therefore, in randomized controlled trial, we compared the results between SB and TS for syndesmotic stabilization in patients with acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 25 publications
0
33
0
1
Order By: Relevance
“…Still, 4 studies reported on the postoperative malreduction rate based on bilateral CT imaging. 3,19,30,35 Three studies reported lower malreduction rates for the suture button group, 3,29,35 and 1 study found no differences. 30 The herein presented study highlights the previously proposed correction potential of the suture button system for both rotation and translation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Still, 4 studies reported on the postoperative malreduction rate based on bilateral CT imaging. 3,19,30,35 Three studies reported lower malreduction rates for the suture button group, 3,29,35 and 1 study found no differences. 30 The herein presented study highlights the previously proposed correction potential of the suture button system for both rotation and translation.…”
Section: Discussionmentioning
confidence: 98%
“… 23 , 36 Today, the authors are aware of 8 RCTs comparing suture button and syndesmotic screw fixation, with 1 study 21 presenting even a 5-year follow-up. 17 When evaluating the clinical outcome of these 8 randomized controlled trials, 3 studies found no differences 17 , 21 , 30 and 5 studies reported superior outcomes for the suture button system for at least 1 clinical outcome parameter. 3 , 7 , 29 , 35 Whether these superior results are because of a higher quality of reduction of the DTFJ remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at the AOFAS score, we found a significant improvement between the two time points. So far, no minimal clinically important difference (MCID) has been specified for ankle fractures [ 42 ]. However, considering the study of Norman et al [ 43 ] it has been assumed as half the standard deviation (SD).…”
Section: Discussionmentioning
confidence: 99%
“…The debate regarding a suture button compared with a single syndesmotic screw for stabilization of syndesmosis disruption has continued in 2 different RCTs 22,23 . Both studies utilized functional scores and radiography, including computed tomographic (CT) scans.…”
Section: Anklementioning
confidence: 99%